Characterisation of M2e Antigenicity using anti-M2 Monoclonal Antibody and anti-M2e Polyclonal Antibodies - Sumarningsih Sumarningsih; Simson Tarigan; Hemmatzadeh Farhid; Jagoda Ignjatovic (Indonesian Center for Animal Research and Development (ICARD), 2019)
Matrix 2 ectodomain (M2e) protein is a potential antigen for detection of influenza A virus infection in vaccinated poultry (DIVA test). However the M2e antigenicity and immune response it induces in either humans or animals are poorly understood. Seventeen M2e peptides and sixteen recombinant M2e (rM2e) proteins with amino acid (aa) changes introduced at position 10, 11, 12, 13 14, 16, 18 and 20 were compared by western blot (WB) and enzyme-linked immunosorbent assay (ELISA) using mouse anti-M2 monoclonal antibody (mAb) 14C2, and anti-M2e peptide chicken and rabbit polyclonal antibody (pAb). The mAb 14C had the best discriminating power and indicated that all six positions contributed to the M2e antigenicity. Position 11 was the important immunodominant and affected Mab14C binding to a greatest degree. Changes in the adjacent position 14, 16 and 18 also influenced the binding, and it detected regardless of the method (WB or ELISA), or the antigen used (M2e peptide or rM2e). For chicken pAb and rabbit pAb, the immunodominant aa was position 10 and the antibody reaction was not affected by aa change at 11. The binding of rabbit pAb was also affected by changes at 14 and 16, which confirm the contribution of these positions to the M2e antigenicity. Position 10 was the only important position for the binding of chicken pAb to M2e. Overall, the study showed that the M2e antigenic sites are located between residues 10 – 18 and that aa changes at position 10, 11, 12, 14, 16 and 18 may all affect the antibody binding within the M2e protein.